2007
DOI: 10.1111/j.1600-0781.2007.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for the treatment of actinic cheilitis

Abstract: Although actinic cheilitis is a common disease, it should be treated carefully because it can undergo malignant transformation. We report a case of actinic cheilitis treated with photodynamic therapy (PDT) using 5-aminolevulinic acid (ALA), with satisfactory outcome in both clinical and pathological aspects. Actinic cheilitis is a pathologic condition affecting mainly the lower lip caused by long-term exposure of the lips to the UV radiation in sunlight. Analogous to actinic keratosis of the skin, actinic chei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 6 publications
1
21
0
1
Order By: Relevance
“…46,48,49 Most studies reported an incubation period of 2 to 4 hours under occlusion, with 3 hours most commonly reported. 14,41,42,48,50 Studies using MAL and red light most commonly reported a treatment dose of 37 J/cm 2 with a range of 37 to 80 J/cm 2 , irradiances ranging from 70 to 192 100 mW/cm 2 for treatment periods of 7 to 12 minutes at a distance of 5 to 7 cm (Table 1). 37 Several studies examined lesions under fluorescent light to ensure absorption of the photosensitizing cream before irradiation.…”
Section: Treatment Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…46,48,49 Most studies reported an incubation period of 2 to 4 hours under occlusion, with 3 hours most commonly reported. 14,41,42,48,50 Studies using MAL and red light most commonly reported a treatment dose of 37 J/cm 2 with a range of 37 to 80 J/cm 2 , irradiances ranging from 70 to 192 100 mW/cm 2 for treatment periods of 7 to 12 minutes at a distance of 5 to 7 cm (Table 1). 37 Several studies examined lesions under fluorescent light to ensure absorption of the photosensitizing cream before irradiation.…”
Section: Treatment Techniquesmentioning
confidence: 99%
“…14,41,42,48,50 Studies using MAL and red light most commonly reported a treatment dose of 37 J/cm 2 with a range of 37 to 80 J/cm 2 , irradiances ranging from 70 to 192 100 mW/cm 2 for treatment periods of 7 to 12 minutes at a distance of 5 to 7 cm (Table 1). 39,44,45,50 To mitigate pain during treatment, 2 studies using ALA and MAL with red light reported use of analgesia 1 hour before irradiation. 37 The 2 studies using ALA with red light reported a fluence of 40 J/cm 2 and an irradiance of 80 mW/cm 2 .…”
Section: Treatment Techniquesmentioning
confidence: 99%
“…Despite these facts, PDT for AC is not very common; there are only few case series and studies that report the applicability and efficacy of this treatment modality for AC 9–15 …”
Section: Introductionmentioning
confidence: 99%
“…Patients were all male farmers, mean age 65AE4 years (range 60-71), with a mean disease duration of 3AE7 years (range [1][2][3][4][5][6][7][8]. Clinical changes at baseline included grey-white thickened, dry and fissured plaques, superficial erosions, crusting and constant scaling and permanent fissuring.…”
mentioning
confidence: 99%